Cafe Agapita: terminal year-end report of a family business - Baranda, Trisha Marie A. (Animo Repository, 2021)
This terminal report discusses in detail the marketing plans/strategies for Cafe Agapita, a family-owned coffeehouse in Silang, Cavite.